Investigation on law of oil production by spontaneous imbibition and water flooding in ultra-low permeability sandstone reservoirs - CHEN Hui (Youqi dizhi yu caishoulu)
Pressure drive-based water injection technology has solved the problem of “no injection and no production” in ultra-low permeability sandstone reservoirs in Shengli Oilfield， but the law of oil-water displacement and the percentage of oil production in pores at different scales in the process of pressure drive-based shut-in and water flooding are still unclear. In order to solve the above problems， spontaneous imbibition and water flooding experiments were carried out in the ultra-low permeability sandstone reservoirs in Dongying Sag， and the evolution characteristics of oil-water distribution during imbibition and water flooding were studied by high temperature and high pressure nuclear magnetic resonance （NMR）. The results show that the T2 spectrum of saturated oil in ultra-low permeability sandstone in Dongying Sag is mainly divided into single peak and double peak， and the double peaks are further divided into left peak height and right peak height. The most oil phase in the pores of the sandstones with an unimodal T2 spectrum and network pore structure can be produced through spontaneous imbibition during shut-in. For sandstones with a bimodal T2 spectrum and dendritic pore structures， a large amount of oil phase is still unproduced after spontaneous imbibition， and the oil recovery can be further improved by water flooding. The oil in micropores and mesopores can be produced through spontaneous imbibition， but the contribution of oil recovery in macropores to total oil recovery is less. When spontaneous imbibition is followed by water flooding， the recovery is further improved， and more oil in macropores and mesopores is produced， but the oil in micropores is less produced.